Burden of Noise-Induced Hearing Loss among Rice Mill Workers in Sokoto State, Northwest Nigeria - Azees, Ayotunde; Ango, Jessica; Isa, Abdulfattah; Adeniyi, Makinde (Nigerian Journal of Basic and Clinical Sciences, 2026)
Context:Work heavily impacts workers' health globally, with noise-induced hearing loss (NIHL) increasingly becoming a major public health concern.Aim:This study accessed the prevalence and predictors of noise-induced hearing impairment among local rice mill workers in Sokoto State, Northwest Nigeria.Materials and Methods:This cross-sectional study was conducted among rice mill workers between June 2019 and July 2019. Participants were selected using a multistage sampling technique, and a pretested interviewer-administered questionnaire was used for data collection. Data were analyzed using IBM®Statistical Package for the Social Sciences (SPSS) version 22, and the results were presented in tables and figures. Statistical tests of associations were conducted using the Chi-square test and binary logistic regression with a significance level set atP< 0.05.Results:The noise level in the rice mills ranged from 81.8 dBA to 91.7 dBA, with a mean of 86.7 ± 2.3 dBA. A hundred and eighty-five respondents (46.5%) of the 398 respondents had at least a symptom of hearing loss, with tinnitus (145 (36.4%)) being the most prevalent. About a third of 125 (32.5%) had hearing impairment in at least one of the ears on audiometry. The predictors of hearing impairment on audiometry were cigarette smoking, education, and having symptoms of hearing loss.Conclusion:The burden of noise-induced hearing impairment is high among rice mill workers in Sokoto State, Northwest Nigeria; hence, both the government and rice mill owners need to initiate smoking cessation programs, promote the use of personal protective equipment, and urgently implement hearing conservation programs to address the problem.
Keywords: Burden; hearing impairment; Northwest Nigeria; rice mill workers; tinnitus